Comprehensive characterization of a Canadian cohort of von Hippel‐Lindau disease patients. Issue 5 (6th August 2019) - Salama, Yasser; Albanyan, Saleh; Szybowska, Marta; Bullivant, Garrett; Gallinger, Bailey; Giles, Rachel H.; Asa, Sylvia; Badduke, Chansonette; Chiorean, Andreea; Druker, Harriet; Ezzat, Shereen; Hannah‐Shmouni, Fady; et al.
Abstract: Von Hippel‐Lindau disease (VHL) is a heritable condition caused by pathogenic variants in VHL and is characterized by benign and malignant lesions in the central nervous system (CNS) and abdominal viscera. Due to its variable expressivity, existing efforts to collate VHL patient data do not adequately capture all VHL manifestations. We developed a comprehensive and standardized VHL database in the web‐based application, REDCap, that thoroughly captures all VHL manifestation data. As an initial trial, information from 86 VHL patients from the University Health Network/Hospital for Sick Children was populated into the database. Analysis of this cohort showed missense variants occurring with the greatest frequency, with all variants localizing to the α‐ or β‐domains of VHL . The most prevalent manifestations were central nervous system (CNS), renal, and retinal neoplasms, which were associated with frameshift variants and large deletions. We observed greater age‐related penetrance for CNS hemangioblastomas with truncating variants compared to missense, while the reverse was true for pheochromocytomas. We demonstrate the utility of a comprehensive VHL database, which supports the standardized collection of clinical and genetic data specific to this patient population. Importantly, we expect that its web‐based design will facilitate broader international collaboration and lead to a better understanding of VHL. Abstract : VHL database generation and analysis algorithm and outputs.